Local Resources Utilization For Planting Media Materials In Limapuluh Kota As A Replacement For Rockwool On Pakchoy ( Brassica rapa L ) Growth And Production - Fedri Ibnusina; Nofrianil Nofrianil (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2022)
The development of technology in agriculture is currently speedy, with innovations that can increase the production and quality of agricultural products. Supporting the hydroponic cultivation system's success is by applying porous and well-aerated media and the availability of sufficient nutrients for plant growth and plant production. The availability of Rockwool is difficult to obtain in the 50 Kota Regency. It needs to utilize local potential as a planting medium alternative, such as using bricks and husk charcoal. The research was conducted in a completely randomized design with three replications. The treatments tested for the composition of the growing media using the Drip flow technique (DFT) system included: Rockwool, Husk Charcoal (50%) + Bricks (50%), Husk Charcoal (25%) + Bricks (75%). Based on the results and discussion of the analysis previously described, the conclusions obtained from the research that has been carried out are as follows: Treatment of the use of various types of growing media on the observation of growth and production of hydroponic Pakcoy plants gives significantly different results on the observation variables of leaf length, leaf width, and the number of leaves and plant total wet weight.